GPS supported assessment integrated with GIS service area analysis of healthcare institutions of Basona Werana in comparison with Debre Berhan - Mindahun, Wondwossen; Agegnehu, Natnael; Nigussie, Andnet (Geodesy and Cartography, 2022)
The study is principally aimed to assess and analyse the spatial location of the health institutions from lowerlevel Health Posts (HPs) to higher level Referral Hospitals (RHs) in both Zonal Capital Debre Berhan Town (DBT) and the surrounding Rural Basona Werana Wereda (BWW) which includes both government and private owned using Global Positioning System (GPS) equipment and ArcGIS software. The methodological procedure encompasses adjustments of data before use for the analysis, data processing, analysis and final result. On this basis, it could become possible to identify the spatial locations of the health institutions in BWW and DBT including residential areas in both districts. Built up road network data set enabled generation of possible service areas and as a result higher Clinics, Health Centrers and hospitals are either nearly or fully provided for urbanized population of DBT while they are either extremely rare or not provided in the rural population of BWW. Absence of road infrastructures and transport facilities also intensified the rural health service access. The study suggests involvement of scientific approaches of GPS, GIS and other relevant technologies towards health policy implementation will be a remedial action for the government and stake holders of the health sector.